AWARENESS REGARDING DIABETES AND ITS MANAGEMENT AMONGST PATIENTS VISITING TERTIARY CARE HOSPITALS AND ITS IMPACT ON GLYCEMIC CONTROL: Diabetes and its Management Awareness - Khan, Anum; Arshad, Abdul Rehman; Farooq, Asif; Raashid, Sheharyar (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess factors affecting disease awareness in diabetics, and its association with glycemic control.Study Design: Cross-sectional analytical study.Place and Duration of Study: Department of Medicine, Pak Emirates Military Hospital Rawalpindi from Jan to Apr 2019.Methodology: Outdoor patients with type-II diabetes mellitus were selected using a consecutive sampling technique. Disease awareness was assessed with a modified Diabetes Knowledge Questionnaire, with scores >70% considered satisfactory. Recent HbA1c levels were used to determine glycemic control (